Synthesis of Adamantane‐Based Trimeric Benzoboroxoles. Issue 28 (15th August 2013) - Claes, Dorith; Holzapfel, Malte; Clausen, Nadine; Maison, Wolfgang
Abstract: Benzoboroxoles are known to bind 1, 2‐diol motifs in carbohydrates in an aqueous environment. Their binding properties have been shown to be dependent on additional recognition sites such as peptides and the number of binding epitopes. In this paper we describe the synthesis of trimeric benzoboroxoles based on a rigid adamantyl core structure. The conjugates are assembled using copper‐catalyzed click reactions of azide scaffolds with alkynyl‐functionalized benzoboroxoles. The design of our trimeric benzoboroxoles followed a biomimetic principle and imitates the trimeric structure of some natural carbohydrate binding proteins (lectins). With an assortment of appropriately functionalized (3 + 1) adamantane scaffolds, trimeric benzoboroxoles have been generated which were combined with additional functional molecules such as dyes and peptides. In summary, we report a highly effective synthetic approach to modular trimeric boronolectines for the assembly of carbohydrate sensors. Abstract : Following a biomimetic design principle, multivalent benzoboroxoles with a tripodal carbohydrate recognition domain have been synthesized. The key step is a microwave‐assisted click reaction of adamantyl scaffolds with an alkynyl‐substituted benzoboroxole.